Redesigned crinkle washer for piezoelectric energy generation - Crawley, Fergus; Ibrahim, Khalifa; Qin, Qing; Luo, Zhenhua (Frontiers in Mechanical Engineering, 2025)
Structures are used for piezoelectric energy harvesters as a way of redirecting the path of an inputted force so that the piezoelectric element can better convert the mechanical energy to electrical energy. A popular structure used for energy harvesting in compressive force scenarios are the cymbal structure or disc spring due to larger spring rates and the ability to turn compression into radial expansion and thus create surface radial tensile stress on the face plane of a piezoelectric element which has been identified as a beneficial characteristic. The drawbacks of the cymbal washer are found when multiplying the washer in a stack configuration, as the shape of the cymbal is only able to activate a single face and the shape creates increased open space which affects power density of an energy harvesting system. This research is further investigating the wave (crinkle) washer and understanding the benefits of a washer that has a rotational symmetry which a single washer can be used to radially stress two piezoelectric elements simultaneously during compressive loading. Simulations show the iterations of the currently available crinkle washer, adjusting design parameters such as curvatures and waves to create an optimised structure resembling a hyperbolic paraboloid washer. The double piezo compression set up was then simulated to receive an area force of 1000 N/m2 vertically onto the top steel backing plate with a diameter of 22 mm and an area of 380 mm2 to demonstrate a total compressive load of 0.38 N, and resulted significant performance improvements. The final optimised circular disc washer charged two 10 nF capacitors to 1.13 mV and 0.89 mV, compared to just 0.01 mV and 0.009 mV achieved with the standard crinkle washer, the performance boost was achieved by removing internal stresses found to be localised to the internal diameter wave radii. The optimised novel crinkle hyperbolic paraboloid configuration was further optimised with slits to eliminate inner stress regions between wave peaks, vastly improving both power density and overall energy harvesting performance with final capacitor voltages of 16.03 mV and 19.77 mV.